Thermoelectric Properties of Ca1−xGdxMnO3−δ (0.00, 0.02, and 0.05) Systems - Ankam Bhaskar; Chia-Jyi Liu; J. J. Yuan (The Scientific World Journal)
Polycrystalline samples of Ca1−𝑥Gd𝑥MnO3−𝛿 (𝑥=0.00, 0.02, and 0.05) have been studied by X-ray diffraction (XRD), electrical resistivity (ρ), thermoelectric power (S), and thermal conductivity (κ). All the samples were single phase with an orthorhombic structure. The Seebeck coefficient of all the samples was negative, indicating that the predominant carriers are electrons over the entire temperature range. The iodometric titration measurements indicate that the electrical resistivity of Ca1−𝑥Gd𝑥MnO3−𝛿 correlated well with the average valence of Mn𝑣+ and oxygen deficiency. Among the doped samples, Ca0.98Gd0.02MnO3−𝛿 had the highest dimensionless figure of merit 0.018 at 300 K, representing an improvement of about 125% with respect to the undoped GaMnO3−𝛿 sample at the same temperature.